Determinants of cervical cancer knowledge and barriers to human papillomavirus vaccine uptake among female university students: A cross-sectional study - Andrew Donkor; Loretta Pokua Osei; Ewura Adwoa Kwafoa Acquaah-Arhin; Pamela Deladem Suka; Doris Kitson-Mills; Alberta Naa Afia Adjei; Evans Ohemeng; Samiratou Ouedraogo; Veronica Millicent Dzomeku (Women's Health)
Background: Cervical cancer is the second most common female cancer in Ghana. Cervical cancer is preventable through knowledge, vaccination against the human papillomavirus (HPV), screening and treatment of precancerous lesions. Objective: This study aimed to assess the determinants of cervical cancer knowledge and barriers to HPV vaccine uptake among female university students in Ghana. Design: An anonymous, online cross-sectional study was conducted from 25 June to 22 September 2024. Methods: The survey contained questions on demographic characteristics, cervical cancer risk factors, symptoms, HPV vaccination and barriers to vaccine uptake. Binomial logistic regression analysis was performed to predict the factors associated with knowledge of cervical cancer. A p -value of less than 0.05 was considered statistically significant. Results: A total of 1662 female university students responded to the online survey. The mean age of the respondents was 21.5 ± 2.03 years. Overall, the prevalence of inadequate knowledge of cervical cancer was 60.2%. The least recognised cervical cancer symptom was blood in the stool or urine (58.4%). Respondents who had a steady partner and living together had 3.59 times higher odds of inadequate knowledge of cervical cancer compared to respondents who were not dating. Muslim respondents had 2.13 times higher odds of inadequate knowledge of cervical cancer compared to Christian. Unvaccinated respondents had 3.85 times higher odds of inadequate knowledge of cervical cancer compared to those who had received the HPV vaccine. More than four-fifths (87.0%) of the respondents indicated that they had not been vaccinated against HPV. The major barriers to HPV vaccine uptake included: inadequate knowledge of the vaccine, fear of side effects, lack of knowledge about the vaccination site, fear of injection and doubts regarding the vaccine’s efficacy. Conclusion: Improving access to cervical cancer awareness and HPV vaccination among university students is a critical public health goal to reduce the incidence of cervical cancer. It is important to promote a free national school-based HPV vaccination programme. Multi-component school-based educational interventions, including traditional methods such as lectures, group discussions and digital tools like web-based educational platforms should be implemented to improve cervical cancer knowledge among university students.